Study of machining indentations over the entire surface of a target ball using the force modulation approach. (21st May 2021) - Wang, Yuzhang; Geng, Yanquan; Li, Guo; Wang, Jiqiang; Fang, Zhuo; Yan, Yongda
Abstract: A modified five-axis cutting system using a force control cutting strategy was to machine indentations in different annuli on the entire surface of a target ball. The relationship between the cutting depths and the applied load as well as the microsphere rotation speed were studied experimentally to reveal the micromachining mechanism. In particular, aligning the rotating center of the high precision spindle with the microsphere center is essential for guaranteeing the machining accuracy of indentations. The distance between adjacent indentations on the same annulus and the vertical distance between adjacent annuli were determined by the rotating speed of the micro-ball and the controllable movement of the high-precision stage, respectively. In order to verify the feasibility and effect of the proposed cutting strategy, indentations with constant and expected depths were conducted on the entire surface of a hollow thin-walled micro-ball with a diameter of 1 mm. The results imply that this machining methodology has the potential to provide the target ball with desired modulated defects for simulating the inertial confinement fusion implosion experiment.